ANALISIS PERSEPSI DAN MOTIVASI KERJA FRESH GRADUATED TERHADAP DUNIA KERJA - Leo Alexander Tambunan (Universitas Bunda Mulia, 2017)
This research discuss about perception and working of motivation analysis for fresh graduated at private university in Jakarta, Results this research is process Questioner from 67 respondent, and SPSS 26. 10 items statement talk about perception and working of motivation for fresh graduated. Respondent fill the questioner use the likert scale. For 10 items statement, salary, bonus, style, location, security, opportunity promotion, environment of work, independent, Team work. This research based on the descriptive statistic. Key Words- Perception, Motivation work, Fresh Graduated